Design and optimization of a Tesla pump for ORC applications - Anselmi Palma, Eduardo; Fiaschi, Daniele; Nicotra, Giovanni; Talluri, Lorenzo (Technical University of Munich, 2021)
The Tesla pump is bladeless turbomachinery known for being more resistant to work with hard-to-pump fluids than conventional turbomachinery, thanks to its simple, robust mechanical design and its working principle (viscous forces). A 2D numerical model is developed and a design procedure of a Tesla pump working with several working fluids (water, R1233zd(E), R1234yf) is proposed. A complete design methodology is developed by evaluating the losses of each component and by introducing a rotor model. The main optimizing parameters of the pump are highlighted and assessed and validation of the model with available experimental results is carried out. A design procedure for a Tesla pump prototype is showed and its characteristic curves are obtained and discussed. The results achieved are similar to other experimental Tesla pumps, with a maximum achieved efficiency of 26.8%. The extension of the model to organic working fluids allowed to predict pump efficiencies higher than 50% for low mass flow rate conditions for both assessed fluids.